KEDUDUKAN SERTA FUNGSI DPR DALAM SISTEM KETATANEGARAAN NEGARA REPUBLIK INDONESIA - Muchlisin Muchlisin (Universitas Islam Darul Ulum, 2019)
The Indonesian state has institutions as a reflection of democracy. Which puts people as the holders of sovereignty. The institution is the house of representatives which is incorporated in the legislative power. In determining the membership of the house of representatives, it remains through the electoral mechanism using the electoral system or the election. This research uses normative juridical research by studying the source of primary law and the source of legal sequences that are either legislation or research results to be carried out an institutional theory approach. The institution has the duty and function in the part of the indonesian state administration system to represent the aspirations or interests of the people. In addition to the duties and function of these institutions have rights that are not owned by other institutions.